KNOWLEDGE OF NURSES REGARDING FIRST AID MANAGEMENT OF BURN INJURY: A CROSS-SECTIONAL STUDY AT BURN UNIT, SAIDU TEACHING HOSPITAL, SWAT (The Research of Medical Science Review, 2025)
Background of the study: Burn wound is significant public health concern worldwide, accounting for round about 180,000 mortalities annually, according to the World Health Organization (WHO).1Most burn-related mortalities occur in under developing countries, where access to dedicated care and resources is imperfect. Worldwide, burn injury is ranked as the fourth leading cause of after road traffic accidents, falls, and interpersonal physical violence among injuries. Method: The research used a cross-sectional study to determine nurse comprehension of burn injury first aid methods at Saidu Teaching Hospital Burn Unit in Swat. Research participants were chosen through a calculation performed using Raosoft online calculator. A survey of 169 registered nurses took place through a confidence interval of 95% and margin of error at 5% and response distribution of 50%. Result: The age distribution of participants was across three age groups: 24–27 years, 28–31 years, and 32–35 years. Majority, 68.05%, of the participants were married, while the remaining 31.95% were unmarried. This indicated that most of the respondents in the study belonged to the married category, with a smaller proportion being unmarried. Data was collected from nurses of different wards. 59.17 % of the participants were from ward, 5.33% were from burn unit. 22.49 % and 13.02 % were from ICU and emergency department respectively. Discussion: The findings of this study reveal a high overall knowledge level (75.15%) among nurses regarding the management of burn patients, with demographic and significantly to variations in knowledge. These results are encouraging, especially when compared to a similar study conducted in Peshawar, where only 56% of participants demonstrated good knowledge, with 32% showing average knowledge and 12% reporting low knowledge. This discrepancy highlights potential differences in educational programs, training opportunities, and clinical exposure between the two settings.